Accurate ultrasonic range measurement using MLS-modulated continuous waves. (January 2015) - Huang, Z.G.; Qiao, C.J.; Wang, Y.K.
Highlights: A method for ultrasonic ranging using MLS-modulated continuous waves is proposed. The MLS-modulated continuous waves are helpful to suppress echoes. The synergy of cross-correlation and DFT methods leads to a higher accuracy. The uncertainty in the measured velocity depends on the thermometer resolution. The distance uncertainty lies on the measured TOF and velocity uncertainties. Abstract: Ultrasonic range measurement has the potential to obtain higher accuracy results while using continuous-wave signals due to its favorable capability of noise resistance. But in short distance ranging applications especially in the space-limited fields, there usually exists strong multiple echoes which will decline the distance measurement accuracy seriously. This paper presents a method to solve this problem through utilizing MLS-modulated continuous-wave signals. Meanwhile, this paper applies a combination of the cross-correlation method and phase shift technique for the high-resolution ultrasonic distance measurement. The synergy above would lead to very popular results. For example, the uncertainty in the measured distance is less than 40 μm for distances up to 200 mm in distilled water.